EXPLORING CHARACTER EDUCATION THROUGH LIU CHUNCE’S JOURNEY IN “BIG WORLD (2024)” MOVIE - Della, Maria; Tawarik, Oxtapianus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study aims to examine the character education values portrayed in the film Big World (2024), focusing on the life journey of Liu Chunce, a teenager with cerebral palsy who faces various physical and social challenges. This topic is particularly significant as film media has the potential to serve as an effective tool for conveying moral messages and shaping character, especially among younger generations. The research employs a qualitative descriptive method with a content analysis approach based on the framework of Mayring and Fenzl. The analysis focuses on 26 character values identified by the Ministry of Education and Culture of the Republic of Indonesia. Data were collected through documentation and analyzed by identifying dialogues, actions, and experiences of Liu Chunce that represent moral values. The findings reveal that 13 character values, such as discipline, perseverance, patience, independence, social care, and leadership, are prominently reflected in the protagonist’s behavior. These values are demonstrated through Chunce’s perseverance, empathy, honesty, and optimism despite his physical limitations. The results suggest that Big World is not only a cinematic work but also an educational medium that can be utilized in character education, particularly within the context of inclusive and values-based learning. This research is expected to contribute to educators, researchers, and education practitioners in integrating film media into instructional strategies that foster positive character development. ABSTRAK Penelitian ini bertujuan untuk mengkaji nilai-nilai pendidikan karakter yang ditampilkan dalam film Big World (2024), dengan fokus pada perjalanan hidup Liu Chunce, seorang remaja penyandang cerebral palsy yang menghadapi berbagai tantangan fisik dan sosial. Topik ini menjadi penting karena media film berpotensi menjadi sarana efektif untuk menyampaikan pesan moral dan membentuk karakter, khususnya bagi generasi muda. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan analisis isi berdasarkan teori Mayring dan Fenzl. Analisis diarahkan pada 26 nilai karakter yang ditetapkan oleh Kementerian Pendidikan dan Kebudayaan Republik Indonesia. Data diperoleh melalui dokumentasi dan dianalisis dengan mengidentifikasi dialog, tindakan, serta pengalaman Liu Chunce yang merepresentasikan nilai-nilai moral. Hasil penelitian menunjukkan bahwa 13 nilai karakter, seperti disiplin, ketekunan, kesabaran, kemandirian, kepedulian sosial, dan kepemimpinan, secara dominan tercermin dalam perilaku tokoh utama. Nilai-nilai ini ditunjukkan melalui ketekunan, empati, kejujuran, dan optimisme Chunce meskipun memiliki keterbatasan fisik. Temuan ini mengindikasikan bahwa Big World bukan hanya karya sinematik, tetapi juga media edukatif yang dapat dimanfaatkan dalam pembelajaran karakter, khususnya pada konteks pendidikan inklusif dan berbasis nilai. Penelitian ini diharapkan dapat memberikan kontribusi bagi pendidik, peneliti, dan praktisi pendidikan dalam mengintegrasikan media film ke dalam strategi pembelajaran yang menumbuhkan karakter positif.